Gambaran kepuasan pasien pada mutu pelayanan kesehatan di puskesmas Pattallassang - Utami, Hasniah Rezki; Ayumar, Andi; Dewi, Chitra (Holistik Jurnal Kesehatan, 2025)
Background: Quality of health services is the level of health services for individuals and communities that can improve optimal health outcomes. Patient satisfaction is the result of patient opinions and assessments of the performance of services provided by health care facilities. Quality health services and affordable costs according to the purchasing power of the community and paying attention to intervention standards that are considered safe are very much needed by patients and the community. Purpose: To determine the description of patient satisfaction with the quality of health services at the Pattallassang Health Center. Method: A descriptive observational study using accidental sampling technique was conducted at Pattallassang Health Center in December 2022 - February 2023 with a population of 1,555 patients and a sample of 318 patients through filling out a questionnaire and analyzed using univariate analysis. Results: The majority of respondents were aged 19-59 years (91.5%), female gender as many as 231 respondents (72.64%) with high school education/equivalent as many as 183 respondents (57.5%), and housewife occupation as many as 159 respondents (50.0%). The level of patient satisfaction in the responsiveness quality dimension who felt quite satisfied was 316 respondents (99.4%), the level of patient satisfaction in the reliability quality dimension who felt quite satisfied was 318 respondents (100%), the level of patient satisfaction in the assurance quality dimension who felt quite satisfied was 318 respondents (100%), the level of patient satisfaction in the empathy quality dimension who felt quite satisfied was 317 respondents (99.7%) and the level of patient satisfaction in the tangible quality dimension who felt quite satisfied was 317 respondents (99.7%). Conclusion: The quality dimensions of responsiveness, reliability, assurance, empathy, and tangible showed that respondents were quite satisfied with the health service facilities.   Keywords: Health Facilities; Quality of Service; Satisfaction.   Pendahuluan: Mutu pelayanan kesehatan merupakan tingkat layanan kesehatan untuk individu dan masyarakat yang dapat meningkatkan luaran kesehatan secara optimal. Kepuasan pasien adalah hasil pendapat dan penilaian pasien terhadap kinerja pelayanan yang diberikan oleh fasilitas pelayanan kesehatan. Pelayanan kesehatan yang bermutu dan biaya terjangkau sesuai daya beli masyarakat serta memperhatikan standar intervensi yang dianggap aman sangat dibutuhkan oleh pasien dan masyarakat. Tujuan: Untuk mengetahui gambaran kepuasan pasien terhadap mutu pelayanan kesehatan di Puskesmas  Pattallassang. Metode: Penelitian observasional deskriptif dengan menggunakan teknik accidental sampling dilakukan di Puskesmas Pattallassang pada bulan Desember 2022–Februari 2023 dengan jumlah populasi sebanyak 1,555 pasien dan  sampel sebanyak 318 pasien melalui pengisian kuesioner dan dianalisis menggunakan analisis univariat. Hasil: Mayoritas responden berusia 19-59 tahun (91.5%), jenis kelamin perempuan sebanyak 231 responden (72.64%) dengan pendidikan SMA/sederajat sebanyak 183 responden (57.5%), dan pekerjaan IRT sebanyak 159 responden (50,0%). Tingkat kepuasan pasien pada dimensi mutu responsiveness (cepat tanggap) yang merasa cukup puas sebanyak 316 responden (99.4%), tingkat kepuasan pasien pada dimensi mutu reliability (kehandalan) yang merasa cukup puas sebanyak 318 responden (100%), tingkat kepuasan pasien pada dimensi mutu assurance (jaminan) yang merasa cukup puas sebanyak 318 responden (100%), tingkat kepuasan pasien pada dimensi mutu empathy (empati) yang merasa cukup puas sebanyak 317 responden (99.7%) dan tingkat kepuasan pasien pada dimensi mutu tangible (bukti fisik) yang merasa cukup puas sebanyak 317 responden (99.7%). Simpulan: Dimensi mutu responsiveness (daya tanggap), reliability (kehandalan), assurance (jaminan),  emphaty (empati), dan tangible (bukti langsung), didapatkan penilaian responden sudah cukup puas terhadap fasilitas pelayanan kesehatan.   Kata Kunci: Fasilitas Kesehatan; Kepuasan; Mutu Pelayanan.